A method for predicting solutions in case-based problem solving - Hüllermeier, Eyke (in Proceedings EWCBR-2000, 5th European Workshop on Case-Based Reasoning, Trento, Italy)

Flexible control of case-based prediction in the framework of possibility theory - Dubois, D.; Hüllermeier, Eyke; Prade, H. (in Proceedings EWCBR-2000, 5th European Workshop on Case-Based Reasoning, Trento, Italy)

Knowledge-based extrapolution of cases: A possibilistic approach - Hüllermeier, Eyke; Dubois, D.; Prade, H. (In Proceedings IPMU-2000 8th International Conference on Information Processing and Management of Uncertainty in Knowledge-Based Systems, Madrid, Spain)

Europarecht - Das Casebook - Krimphove, Dieter; Pieper, Stefan Ulrich; Schollmeier, Andres

Fuzzy dynamics and applications in biological systems modelling - Hüllermeier, Eyke; Giersch, C. (Systems Analysis, Modelling, Simulation)

Evaluation and specification of a synergetic business cycle model with German data - Hüllermeier, Eyke; Kraft, M.; Weise, P. (Homo Oeconomicus XVI)

Formalizing case-based inference using fuzzy rules - Dubois, D.; Hüllermeier, Eyke; Prade, H. (Soft Computing in Case-Based Reasoning)

Personalführung und Organisation

Von der Hollerith-Maschine zum Parallelrechner - Die alltägliche Aufgabe des Sortierens als Fortschrittsmotor für die Informatik - Meyer auf der Heide, Friedhelm; Wanka, Rolf (ForschungsForum Paderborn)

Hardwarepraktikum im Diplomstudiengang Informatik - Hellebrand, Sybille; Wunderlich, Hans-Joachim

A Mixed Mode BIST Scheme Based on Reseeding of Folding Counters - Hellebrand, Sybille; Liang, Hua-Guo; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

3-DIMENSIONAL DESCRIPTION OF THE MICROSTRUCTURE OF HEATED SURFACES IN NUCLEATE POOL BOILING - Luke, Andrea; Baumhögger, Elmar; Scheunemann, P. (Multiphase Science and Technology)

Bounds for the independence number of critical graphs - Brinkmann, Gunnar; Choudum, Sheshayya A; Grünewald, Stefan; Steffen, Eckhard (Bull. London Math. Soc.)

A refinement of Vizing's theorem - Steffen, Eckhard (Discrete Mathematics)

Reductions of Symmetry configurations n3 - Carstens, Hans Georg; Dinski, Thomas; Steffen, Eckhard (Discrete Applied Mathematics)

An Implementation Framework for Run-time Reconfigurable Systems - Eisenring, Michael H.; Platzner, Marco (Proceedings of the 2nd International Workshop on Engineering of Reconfigurable Hardware/Software Objects (ENREGLE))

Optimization of Run-time Reconfigurable Embedded Systems - Eisenring, Michael; Platzner, Marco (Proceedings of the 10th International Workshop on Field Programmable Logic and Applications (FPL))

First-principles study of (2×1) and (2×2) phosphorus-rich InP(001) surfaces - Pulci, Olivia; Lüdge, Kathy; Schmidt, Wolf Gero; Bechstedt, F (Surface Science)

(001) Surfaces of GaP and InP: structural motifs, electronic states and optical signatures - Schmidt, Wolf Gero; Bernholc, J.; Bechstedt, F. (Applied Surface Science)

Angle Resolved Photoemission Spectroscopy of the InP(001) surface - Frisch, A.M.; Vogt, P.; Visbeck, S.; Hannappel, Th.; Willig, F.; Braun, W.; Richter, W.; Bernholc, J.; Schmidt, Wolf Gero; Esser, N. (Applied Surface Science)

Surface phase diagram of (2×4) and (4×2) reconstructions of GaAs(001) - Schmidt, Wolf Gero; Mirbt, S.; Bechstedt, F. (Physical Review B)

Understanding reflectance anisotropy: Surface-state signatures and bulk-related features in the optical spectrum ofInP(001)(2×4) - Schmidt, Wolf Gero; Esser, N.; Frisch, A. M.; Vogt, P.; Bernholc, J.; Bechstedt, F.; Zorn, M.; Hannappel, Th.; Visbeck, S.; Willig, F.; Richter, W. (Physical Review B)

Understanding reflectance anisotropy: Surface-state signatures and bulk-related features - Schmidt, Wolf Gero; Bechstedt, F.; Bernholc, J. (Journal of Vacuum Science & Technology B: Microelectronics and Nanometer Structures)

Step-induced optical anisotropy of Si(111):H surfaces - Schmidt, Wolf Gero; Bernholc, J. (Physical Review B)

Large-Scale Applications of Real-Space Multigrid Methods to Surfaces, Nanotubes and Quantum Transport - Bernholc, J.; Briggs, E. L.; Bungaro, C.; Buongiorno Nardelli, M.; Fattebert, J. -L.; Rapcewicz, K.; Roland, C.; Schmidt, Wolf Gero; Zhao, Q. (Computer Simulation of Materials at Atomic Level)

Scientific Progress and Changes of Order Hierarchies of Scientific Disciplines - Peckhaus, Volker (The Nature of Growth of Mathematical Knowledge)

Kantianer oder Neukantianer? Über die Schwierigkeiten, Frege der Philosophie seiner Zeit zuzuordnen - Peckhaus, Volker (Gottlob Frege — Werk und Wirkung. Mit den unveröffentlichten Vorschlägen für ein Wahlgesetz von Gottlob Frege)

The Contextualism of Philosophy - Peckhaus, Volker (The Sociology of Philosophical Knowledge)

El pragmatismo del programa de Hilbert - Peckhaus, Volker (Cuadernos del Sur. Filosofía)

Self-tuning speed control for servo drives with imperfect mechanical load - Wertz, H.; Schutte, F. (Conference Record of the 2000 IEEE Industry Applications Conference. Thirty-Fifth IAS Annual Meeting and World Conference on Industrial Applications of Electrical Energy (Cat. No.00CH37129))

Analysis of three-phase/three-level rectifiers at low load and discontinuous conduction mode - Ide, P.; Froehleke, N.; Grotstollen, H.; Korb, W.; Margaritis, B. (APEC 2000. Fifteenth Annual IEEE Applied Power Electronics Conference and Exposition (Cat. No.00CH37058))

Dirk Hartmann/Peter Janich (Hgg.), Die Kulturalistische Wende. Zur Orientierung des philosophischen Selbstverständnisses (suhrkamp taschenbuch wissenschaft 1391). Suhrkamp, Frankfurt am Main 1998 - Peckhaus, Volker (Philosophischer Literaturanzeiger)

Werner Stelzner, Gottlob Frege. Jena und die Geburt der modernen Logik. ed. Verein zur Regionalförderung von Forschung, Innovation und Technologie für die Strukturentwicklung e.V., no place [Jena]: ReFIT 1996 - Peckhaus, Volker (Modern Logic)

Online-Schätzung von mechanischen Parametern, Kennlinien und Zustandsgrößen geregelter elektrischer Antriebe - Beinecke, S.

Rivadulla, Andrés, “The Popperian Revolution in the Methodology of Science”, In: Jesús Padilla Gálvez et al. (eds.), Wittgenstein and the Vienna Circle. Proceedings of the International Congress, Toledo, Spain, November 2–5, 1994, Cuenca: Ediciones de la Universidad de Castilla-La Mancha: Cuenca 1998 (Estudios; 49), 305–316 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Mancosu, Paolo, “Between Russell and Hilbert: Behmann on the Foundations of Mathematics”,In: Bulletin of Symbolic Logic 5 (1999), 303–330 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Radu, Mircea, “Justus Grassmann’s Contributions to the Foundations of Mathematics: Mathematical and Philosophical Aspects”, In: Historia Mathematica 27 (2000), 4–35 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Zach, Richard, “Completeness before Post: Bernays, Hilbert, and the Development of Propositional Logic”, In: Bulletin of Symbolic Logic 5 (1999), 331–366 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Glashoff, Klaus, „Das Rad der Gründe — Der Hetucakradamara von Dignaga“, Mitt. Math. Ges. Hamb. 18 (1999), 75–104 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Phraseologische Modifikationen in der Sprache der Presse (am Beispiel der Wochenzei-tungen „Die Woche“ und „Die Zeit“) - Ptashnyk, Stefaniya (Німецька мова в сучасному світі. Матеріали доповідей міжнародної наукової конференції, Дрогобич, 7-9.05.1998)

Zum Begriff der phraseologischen Modifikationen - Ptashnyk, Stefaniya (Kwartalnik neofilologiczny. Zeszyt 3/2000)

Текстотвірні функції фразеологічних модифікацій у газетному тексті [Textkonstituierende Funktionen phraseologischer Modifikationen in den Zeitungstexten – ukr.] - Ptashnyk, Stefaniya (Науковий вісник Чернівецького університету. Випуск 98: Германська філологія)

Decay properties of the one-particle Green function in real space and imaginary time - Schindlmayr, Arno (Physical Review B)
The decay properties of the one-particle Green function in real space and imaginary time are systematically studied for solids. I present an analytic solution for the homogeneous electron gas at finite and at zero temperature as well as asymptotic formulas for real metals and insulators that allow an analytic treatment in electronic-structure calculations based on a space-time representation. The generic dependence of the decay constants on known system parameters is used to compare the scaling of reciprocal-space algorithms for the GW approximation and the space-time method.

Nutzen und Allgemeinheit. Zu einigen grundlegenden Prinzipien der Praktischen Philosophie - Hagengruber, Ruth Edith

Cubito: Der Baukasten zum Bauen und Bewegen, Spielen und Gestalten - Albers, Timm; Miedzinski, Klaus

A Mixed Mode BIST Scheme Based on Reseeding of Folding Counters - Hellebrand, Sybille; Liang, Hua-Guo; Wunderlich, Hans-Joachim (IEEE International Test Conference (ITC'00))

Rituale des Verschwindens. Überlegungen zu Cees Nootebooms Rituale und zu einer Ästhetik der Resignation - van Laak, Lothar (Ästhetische und religiöse Erfahrungen der Jahrhundertwenden III: um 2000)

Klopstocks Furor teutonicus, die Antike und Frankreich - Elit, Stefan (Kulturelle Identität. Über den Zusammenhang zwischen Vergangenheitsdeutungen, Gegenwartsbezug und Zukunftserwartung für die Konstruktion kollektiver Identitäten (Les Travaux du Centre Marc Bloch 18))

Übersetzen als internationaler Dichterwettstreit. Klopstocks Übersetzungen Horazischer Oden als doppelter poetischer Überbietungsversuch - Elit, Stefan (Tradita et Inventa. Beiträge zur Rezeption der Antike)

Gestik. Figuren des Körpers in Text und Bild